2020
DOI: 10.3390/nu12020411
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Centella asiatica Extract on DNCB-Induced Atopic Dermatitis in HaCaT Cells and BALB/c Mice

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease caused mainly by immune dysregulation. This study explored the anti-inflammatory and immunomodulatory effects of the Centella asiatica ethanol extract (CA) on an AD-like dermal disorder. Treatment with CA inhibited the expression of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in a dose-dependent manner in inflammatory stimulated HaCaT cells by interferon-γ (IFN-γ) and TNF-α-triggered inflammation. Eight-week-old BALB/c mice treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…To determine whether the chrysin-induced suppression of CCL5 expression affects the infiltration of inflammatory cells, we performed mast cell staining in DNCB-challenged skin tissue sections using toluidine blue (TB). In accordance with a previous study [ 19 ], DNCB increased the infiltration of TB-positive mast cells; however, this recruitment of TB-positive cells by DNCB was reduced significantly ( p < 0.001, n = 5) upon the repeated application of chrysin ( Figure 6 B). These results suggest that IKK targeting by chrysin led to the suppression of NF-κB activity and reduced NF-κB-regulated CCL5 expression, subsequently suppressing the inflammatory responses and infiltration of inflammatory cells, such as mast cells, in DNCB-induced skin lesions in BALB/c mice.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To determine whether the chrysin-induced suppression of CCL5 expression affects the infiltration of inflammatory cells, we performed mast cell staining in DNCB-challenged skin tissue sections using toluidine blue (TB). In accordance with a previous study [ 19 ], DNCB increased the infiltration of TB-positive mast cells; however, this recruitment of TB-positive cells by DNCB was reduced significantly ( p < 0.001, n = 5) upon the repeated application of chrysin ( Figure 6 B). These results suggest that IKK targeting by chrysin led to the suppression of NF-κB activity and reduced NF-κB-regulated CCL5 expression, subsequently suppressing the inflammatory responses and infiltration of inflammatory cells, such as mast cells, in DNCB-induced skin lesions in BALB/c mice.…”
Section: Resultssupporting
confidence: 92%
“…A histopathological analysis, which involved hematoxylin and eosin (H&E) staining, and a morphometric analysis showed that the DNCB-induced increase in epidermal and dermal thickenings reduced significantly ( p < 0.001, n = 5) upon the topical application of chrysin ( Figure 5 C). Previous studies have reported that DNCB increases the phosphorylation of p65 NF-κB in BALB/c mice models [ 18 , 19 ]. We also observed that the epidermal levels of phosphorylated p65 NF-κB were high in mice challenged with DNCB; however, the levels decreased substantially upon the topical application of chrysin ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the presence of local inflammation in the skin of db/db mice. In particular, the mRNA expression levels of TNF-α, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2), whose expression is increased due to inflammation [23,24], were evaluated as indices of inflammation.…”
Section: Mrna Expression Levels Of Tnf-α Inos and Cox-2 In The Skinmentioning
confidence: 99%
“…At the onset of atopic dermatitis, skin inflammation occurs and the expression levels of inflammatory markers, such as TNF-α, IL-6, iNOS, and COX-2, increase [ 26 , 27 ]. We observed the skin condition and the effect of AP on the inflammatory reactions using these expression levels as indexes ( Figure 3 and Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%